"A Futile Activity": Reflections on Imprisonment in India through Kobad Ghandy's Fractured Freedom: A Prison Memoir (2021). (December 2022) - Darlong Diengdoh, Basil N.
Prison writing in India has not been adequately engaged with, either in its literary bounds or its implications on prison conditions and administration. With the majority of incarcerations consisting of those yet to be found guilty of a crime, the absence of uniform policies or legal provisions concerning these 'undertrials' affects in a consequential way the prisoner's ability to exercise certain rights, even if limited, especially with regard to personal expression. This article explores this aspect through the decade-long incarceration reflected upon by Kobad Ghandy's Fractured Freedom: A Prison Memoir (2021).